PENGARUH MODEL PEMBELAJARAN NUMBER HEAD TOGETHER BERBANTUAN MEDIA KOMIK “FLAT WAKE ADVANTURE” TERHADAP KEMAMPUAN PEMECAHAN MASALAH - Akadiyaningsih, Dwi; Roestika Rini, Zulmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In mathematics learning, problem solving is an important activity when learning mathematics. In mathematics learning, the right media according to the learning model can make the learning process more interesting, easier to understand, according to students' needs. This study aims to examine the effect of the Number Head Together learning model (NHT) assisted by the comic media